Zero-phonon emission bands of solid hydrogen at 6-12 μm wavelength. An astrophysical phenomenon - Schaefer, J. (Физика низких температур, 2009)
Infrared emission bands in the wavelength range of 6–12 μm observed in the ISO-SWS mission are assigned to rotational zero-phonon bands of solid parahydrogen by using Van Kranendonk’s approximate rigid-lattice method. This method is based on superposed electric quadrupole pair interactions and superposed quadrupole induced dipole moments of pairs in the hcp crystal. Accordingly, the approximate formalism uses zero-order H₂ pair wave functions. Symmetry effects of the hcp crystal require preference of rotational pair transitions. The interaction potential of the pairs is confined to the electric quadrupole–quadrupole interaction. Zero-phonon emission bands of H₂ pair transitions fitted to the spectrum contain at least one delocalized j = 2 state initially and/or finally because of their significantly enhanced emission rates. They also yield the characteristic band widths which fit nicely to the widths of the observed features. The frequency positions of the seven pure parahydrogen pair transitions used, obtained from experimentally determined rotational solid hydrogen energy levels, are in perfect agreement with the observed features, whereas the three mixed ortho–para pair transitions need a presently unknown frequency correction, caused by the migration of the ortho-H₂ molecules into the parahydrogen crystal prior to emission, the so-called initial excess binding energies. The astrophysical setup of the observed source is discussed in the end of the paper.
Remove selected